2014
DOI: 10.20344/amp.5141
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index Assessment of Health Care Professionals in a Primary Care Setting in Portugal: a Cross Sectional Study

Abstract: RESUMOIntrodução: A obesidade é um importante problema de saúde pública por ser fator de risco para numerosas doenças e estar associada a maior risco de morte. A evidência sobre a prevalência de excesso de peso em profissionais de saúde é escassa e este grupo é frequentemente esquecido em programas de intervenção. Este trabalho tem como objetivo estimar a prevalência de obesidade e excesso de peso entre os profissionais nos cuidados de saúde primários portugueses e descrever diferenças entre os grupos profissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
2
0
2
Order By: Relevance
“…Likewise, in the study by Kyle et al on healthcare professionals, the highest BMI values were found among other healthcare professionals, who were followed by nurses for this matter [34]. The study by Campos-Matos et al on healthcare professionals found that the group with the highest rate of obesity was other healthcare personnel, followed by allied healthcare personnel [35]. These high rates of obesity among other healthcare personnel and nurses may be explained by the probability that, as these individuals sometimes have to take night shifts, they may be consuming snacks with high energy content, or they may be eating at late hours at night as they get hungry.…”
Section: Discussionmentioning
confidence: 90%
“…Likewise, in the study by Kyle et al on healthcare professionals, the highest BMI values were found among other healthcare professionals, who were followed by nurses for this matter [34]. The study by Campos-Matos et al on healthcare professionals found that the group with the highest rate of obesity was other healthcare personnel, followed by allied healthcare personnel [35]. These high rates of obesity among other healthcare personnel and nurses may be explained by the probability that, as these individuals sometimes have to take night shifts, they may be consuming snacks with high energy content, or they may be eating at late hours at night as they get hungry.…”
Section: Discussionmentioning
confidence: 90%
“…We classified health personnel into four health work roles. A previous study showed that nurses had the highest BMI, followed by doctors and superior technicians 39. Another study focusing on female hospital personnel revealed that overweight was more frequent in cleaning staff (56%) and nursing auxiliaries (36%) than in nurses (24%) and administrative staff (27%) 40.…”
Section: Discussionmentioning
confidence: 94%
“…Что касается метаболических ФР, то врачи Томской области не отличаются по этим показателям от иностранных коллег. Например, частота избы-точной массы тела среди врачей в Томской области аналогичная таковой в Португалии -34,7% vs 38,6% [9], а уровень дислипидемии соответствует таковому в США -27,3% vs 28% [10]. Повышенный уровень глюкозы зарегистрирован всего у 1,6% работников здравоохранения, что несколько выше, чем у врачей из Чехии [11].…”
Section: Discussionunclassified